Experimental Evaluation of Earthworm and Plant Root Soil Penetration–Cavity Expansion Models Using Cone Penetrometer Analogs. Issue 3 (4th March 2016) - Ruiz, Siul; Straub, Isabelle; Schymanski, Stanislaus J.; Or, Dani
Abstract : Core Ideas: Analytic model for penetration–expansion forces closely agrees with measurements. Measurements used cones with size geometry similar to earthworms and roots. Soil parameters and constraints for root and earthworm bioturbation are estimated. To form new burrows, earthworms need to consume 0.3 kg C m −2 yr −1 . Recent mechanical models of soil penetration by earthworms and plant roots based on penetration‐cavity expansion were tested using cone penetration measurements at scales compatible with the sizes of earthworms and plant roots. Measurements using different cone radii (1.0–2.5 mm) and cone semi‐apex angles (15–30°) were obtained for a range of soils and water contents at highly resolved penetration forces and constant insertion rates. The cone penetration measurements were interpreted using independently determined soil mechanical parameters and yielded good agreement with predictions from an analytical mechanical model. Experimental confirmation of penetration force predictions supports estimates of energy costs associated with soil bioturbation that vary with soil hydration status and mechanical characteristics. Effects of soil friction and axial compaction were assessed by comparing the results from conventional and recessed cones (to eliminate soil–shaft friction). The study provides new insights into quantitative soil bioturbation processes and expands predictive capabilities of the mechanics and energetics of earthworm activity and root zone dynamics related to soil structure development.